The correlations among critical thinking skills, critical reading skills and reading comprehension - Mawaddah Hidayati; Rita Inderawati; Bambang Loeneto (English Review: Journal of English Education, 2020)
Critical thinking skills, critical reading skills and reading comprehension were the most crucial life skills that should be mastered by the students, especially for university students. The objectives of this study were: (1) to find out whether or not there was a significant correlation among students critical thinking skills and reading comprehension, (2) to find out whether or not there was a significant correlation among critical reading skills and reading comprehension, and (3) to find out whether or not there was a significant correlation among the predictor variables (critical thinking skills and critical reading skills) and the criterion variable (reading comprehension) of English Education Study Program students of UIN Raden Fatah Palembang. In this study, 90 undergraduate English Education Study Program of UIN Raden Fatah Palembang in the academic year 2018/2019 in the fourth semester were chosen as a sample by means of purposive sampling. This study conducted correlational research design. The data were collected by using tests. Pearson Product Moment correlation and regression were used to analyzed the data. Based on the data collected and analyses applied in this study, the findings revealed that (1) there was a significant correlation among critical thinking skills and reading comprehension with r-value 0.810, (2) there was a significant correlation among critical reading skills and reading comprehension with r-value 0.844, (3) there was a significant correlation among predictor variables (critical thinking skills and critical reading skills) gave 71.3% contribution to criterion variable (reading comprehension).